Overcoming Barriers: Exploring English Learning Anxiety Among 10th-Grade Students at Madrasah Aliyah Balongrejo - Maisarah, Maisarah; Fanani, Achmad; Rachman, Latifah (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2024)
This study investigates the anxiety experienced by 10th-grade students of Madrasah Aliyah Balongrejo Jombang in learning English. The research focuses on five types of anxiety: communication, performance, test, assessment, and comprehension. Using a descriptive quantitative approach, the study highlights significant levels of anxiety among students, including nervousness when speaking English, fear of misunderstanding, and stress during exams. Recommendations are proposed, such as implementing supportive teaching methods, providing psychological interventions, and organizing skill-enhancing programs to mitigate anxiety and improve students' English proficiency.